Transnasal Endoscopic Repair of Posttraumatic Meningoencephalocele: A Rare Presentation - Kaushik, Eshaan; Nayyar, Ankush; Charaya, Kshitij; Jugpal, Tejeshwar Singh (Indian Journal of Neurosurgery, 2024)
Meningoencephalocele is a rare condition that results due to defect in skull base causing brain tissue to herniate along with meninges. We present a case of posttraumatic meningoencephalocele in an 11-year-old child, who presented with nasal mass and cerebrospinal fluid leak. A cribriform plate defect was detected on magnetic resonance imaging along with herniation of brain tissue. The big defect was successfully repaired endoscopically in multiple layers and without placement of a lumbar drain, thereby reducing the complications of an open transcranial surgery.
Keywords: CSF leak; endoscopic skull base surgery; meningitis; meningoencephalocele; nasal Mass; skull base